Occupational Status of Asian Graduates and their Implications to Institutional Curricular Offerings - Rahl – Baldonasa, Marian Benjie (JPAIR Institutional Research, 2017)
Occupational status appears to indicate a reliable and powerful characteristic of persons or households by dint of its temporal stability and substantial correlation with other social and economic variables. This descriptive study determined the occupations of BS Fi graduates and its implications to curricular offerings from school year 2002 to 2011. The standard survey questionnaire checklist was used in obtaining the data. Using descriptive statistics, results showed that majority of the male graduates above 30 years old who graduated before 2007 had permanent occupational status than females. BS Fisheries (BS Fi) graduates acquired a permanent status in their jobs because they had an additional degree like educational units, and master 's degrees in their own field of specialization and other fields. Graduates with educational units and master 's degree in education pursued their teaching careers. Others are employed at government fisheries agencies and other research institutions. Satisfactory working condition, good management, opportunity to travel and high salary are the factors that made graduates stay in their jobs. The university has to augment its instructional facilities and library resources to adequately meet the needs of its students for a more effective program instruction.
Keywords: Tertiary Education and Management; occupational status; descriptive design